O que há por trás da cortina de fumaça? : uma análise sobre a produção de carvão vegetal e silvicultura do eucalipto no município de Cândido Sales - BA - Gomes Neto, João Ferreira (2012)
The main objective of this research is to analyze the relationships (re)produced by capital in the process of appropriation of the work and the nature in charcoal of the municipality of Cândido Sales, state of Bahia. In order to realize the productive dynamic that builds the business reality of charcoal, the method materialisthistorical-dialectical assumption is theoretical-methodological and political development assumed in the study. The indiscriminate exploitation of nature and the overexploitation of labor in the charcoal are a reflection of the objective of reducing the exchange value of the relationship between society-nature subjugated to the (dis)husbands of capital. Due to the decreasing supply of wood from the Atlantic Forest in the municipality, the governmental project of "reforestation" program called Forests for the Future is implemented under the discourse of sustainable development, however is maintaining the supply of steel, barbecue networks and supermarkets in the Southeast of Brazil, buyers of coal produced in clandestine Cândido Sales. Ultimately, it is the capitalist ploy (re)production territory for the appropriation of nature and concrete work, oxygenating the fire and smoke burning the forests and hope the working class in charcoal.